Characterization of melanosomes involved in the production of non-iridescent structural feather colours and their detection in the fossil record. Issue 155 (28th June 2019) - Babarović, Frane; Puttick, Mark N.; Zaher, Marta; Learmonth, Elizabeth; Gallimore, Emily-Jane; Smithwick, Fiann M.; Mayr, Gerald; Vinther, Jakob
Abstract : Non-iridescent structural colour in avian feathers is produced by coherent light scattering through quasi-ordered nanocavities in the keratin cortex of the barbs. To absorb unscattered light, melanosomes form a basal layer underneath the nanocavities. It has been shown that throughout Aves, melanosome morphology reflects broad categories of melanin-based coloration, as well as iridescence, allowing identification of palaeocolours in exceptionally preserved fossils. However, no studies have yet investigated the morphology of melanosomes in non-iridescent structural colour. Here, we analyse a wide sample of melanosomes from feathers that express non-iridescent structural colour from a phylogenetically broad range of extant avians to describe their morphology and compare them with other avian melanosome categories. We find that investigated melanosomes are typically wide (approx. 300 nm) and long (approx. 1400 nm), distinct from melanosomes found in black, brown and iridescent feathers, but overlapping significantly with melanosomes from grey feathers. This may suggest a developmental, and perhaps evolutionary, relationship between grey coloration and non-iridescent structural colours. We show that through analyses of fossil melanosomes, melanosomes indicative of non-iridescent structural colour can be predicted in an Eocene stem group roller ( Eocoracias : Coraciiformes) and with phylogenetic comparative methods the likely hue can be surmised. The overlap between melanosomes from grey and non-iridescent structurally coloured feathers complicates their distinction in fossil samples where keratin does not preserve. However, the abundance of grey coloration relative to non-iridescent structural coloration makes the former a more likely occurrence except in phylogenetically bracketed specimens like the specimen of Eocoracias studied here.